STRATEGI KOMUNIKASI DALAM MENINGKATKAN SRADHA DAN BHAKTI BRAHMACARI PASRAMAN DI ERA DISRUPSI - Suardana, I Ketut Putu; Janarta, I Made Ika (IAHN Gde Pudja Mataram, 2023)
The role of Hindu religious instructors through pasraman is needed to provide counseling to the younger generation of Hindus regarding the negative impacts of technology and information. Pasraman as a place to gain Hindu religious knowledge that is closest to perfection in an effort to increase sradha and bhakti brahmacari pasraman. Although learning at the pasraman has a fixed schedule, the interests and motivations of the brahmacari to attend the pasraman vary. This is partly caused by the way extension agents are still less effective in communicating. The aims of this study: 1) To describe the communication strategy of Hindu religious instructors in increasing sradha and bhakti brahmacari pasraman. 2) To find out the obstacles experienced in implementing the communication strategy by Hindu religious instructors to brahmacari pasraman. 3) To describe the implications of extension communication strategies in increasing sradha and bhakti brahmacari. The object of this research is the communication strategy of extension workers to Brahmacari Pasraman. Data collection methods and techniques used are: descriptive qualitative through observation and interview techniques. The theory used in this study is Lasswell's theory, namely who says what with what channels to whom with how influences. The results of this study: 1) The communication strategy used by extension workers in providing counseling to the Brahmacari is an informative and repetition communication strategy. 2) Communication constraints experienced by extension agents which became obstacles, namely: sematic barriers. 3) Implications of the communication strategy of the extension officers towards the brahmacari have implications for the field of Hindu religion and social functions.